Empire of hell: Religion and the campaign to end convict transportation in the British Empire, 1788-1875. By Hilary M. Carey. Pp. XII + 359 incl. 17 tables. Cambridge-New York, Cambridge University Press, 2019. £75. 978 1 107 04308 4 - Morrison, Hugh (The journal of ecclesiastical history, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS002204692000086X/resource/name/firstPage-S002204692000086Xa.jpg